2018
DOI: 10.1186/s12889-018-5394-9
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional associations between weight-related health behaviors and weight misperception among U.S. adolescents with overweight/obesity

Abstract: BackgroundWeight misperception occurs when there is a discrepancy between one’s actual and perceived weight status. Among adolescents with overweight/obesity, many believe that correcting weight misperception is imperative to inspire weight-related behavior change. However, past research has shown that adolescents with overweight/obesity who misperceive their weight status gain less weight over time compared to accurate perceivers. Therefore, our objective was to examine possible mechanisms underlying this rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 47 publications
(59 reference statements)
1
12
0
1
Order By: Relevance
“…The nonsignificant association between self-perception of body and eating disorder may be due to those who misperceived their body weight could be engaging in positive weight-related health behaviors, such as good and balanced dietary intake, as reported in a cohort study conducted among adolescents in the United States. 27 Trying to lose weight was significantly associated with eating disorder. In a study among younger adult, women were reported to be mostly engaged in sports actively, having strict diets and tried to eat healthy compared with men of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…The nonsignificant association between self-perception of body and eating disorder may be due to those who misperceived their body weight could be engaging in positive weight-related health behaviors, such as good and balanced dietary intake, as reported in a cohort study conducted among adolescents in the United States. 27 Trying to lose weight was significantly associated with eating disorder. In a study among younger adult, women were reported to be mostly engaged in sports actively, having strict diets and tried to eat healthy compared with men of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Government agencies use YRBS data to identify trends in youth risk behaviors and track progress toward meeting national health goals (CDC, 2018a). Many professions, including law, psychology, nutrition and medicine also use YRBS data to make practice and policy recommendations (Dawson, 2018; Hahn, Borton, & Sonneville, 2018; King, Marino, & Barry, 2018; Meyer, Luo, Wilson, & Stone, 2019). However, the use of YRBS data in public health nursing research is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon might be particularly prevalent in AN cases with rapid and severe weight loss. Indeed, both under- and overweight are associated with body size misperception (13, 33), suggesting that extreme weight changes might be associated with an impeded or delayed body image update. On the other hand, body size perception of a substantial proportion of overweight participants is accurate (33), and, hence, body image updates after weight gain are possible.…”
Section: Discussionmentioning
confidence: 99%